A Case Report of Hereditary Angioedema: Challenges in Diagnosis and Management - Alvina Widhani; Suzy Maria; Rifky Yulian; Anshari Saifuddin Hasibuan; Sukamto Koesnoe (Acta Medica Indonesiana, 2023)
Hereditary angioedema (HAE) is a rare autosomal dominant genetic disorder which causes bradykinin mediated angioedema. Although it can be life threatening, HAE may be underdiagnosed due to a lack of awareness of the disease and limited access to laboratory testing. Here, we report a case of HAE which was diagnosed only after the patient was referred for COVID-19 vaccination even though he had been experiencing recurrent angioedema for the past 30 years.